Preferred Learning Styles of Accounting Major Students - Salcedo, Arnold (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The general objective of this research is to determine the learning style of accounting major students of a university in Central Luzon, Philippines, and the corresponding teaching strategy for the identified learning style. By conducting a cross-sectional descriptive research design on learning styles among three hundred fifty-three (353) accounting major students, the combination of learning styles that best describe the accounting major students using Kolb Learning Style Inventory Model is said to be ‘reflector’ style using the diverging strategies which are watching and feeling, following a combination of concrete experiences and reflective observation. The proposed teaching strategies will aid teachers in adjusting their teaching methods that suited for the learning style of accounting major students versus the current teaching methods being received by accounting students today.